PERLUASAN TANGGUNG JAWAB FORMAL KANTOR PERTANAHAN DALAM BALIK NAMA SERTIFIKAT DENGAN ADANYA GUGATAN PIHAK KETIGA (STUDI PUTUSAN MA NO. 3537 K/PDT/2015) - Cynthia, Azani; Muhammad, Yamin; Maria, Kaban (Jurnal Multidisiplin Sosial dan Humaniora, 2025)
Land as an economic resource is an important need for the life of every human being so that people want to own and control land rights as a whole. Land ownership and control rights are the starting point for the emergence of land problems due to land conflicts/disputes between the community and the government as well as between the communities themselves. It is undeniable that there will be problems in the field of land. The Basic Agrarian Law (UUPA) is a statutory regulation that regulates land issues in Indonesia This research is descriptive analysis. Descriptive means that this research is expected to be able to obtain a detailed and systematic description of the problems studied. Research generally aims to describe systematically, factually, and accurately to a particular population or area, regarding certain traits, characteristics or factors. The analysis is carried out based on the description of the facts obtained, a careful analysis will be carried out on how to answer the problem. Certain problems that are intended in this research are problems related to the Extension of Formal Responsibilities of the Land Office Behind the Name of a Certificate in the presence of a Third Party Lawsuit. The parties involved in a civil case must have a legal relationship and in this case the Panel of Judges is of the opinion that it is not necessary to withdraw Notary Fenny Herawati, SH.M.Kn as the Defendant because it is not a party that is bound by the power of attorney agreement and sale and purchase agreement with the repurchase right. As regulated in Article 1340 of the Civil Code "an agreement only applies between the parties who make it". Notary Fenny Herawati, SH.M.Kn in this case only serves as a public official who makes an authentic deed that provides proof of strength for the contents of the agreement made by the parties. Whereas the Head of the Probolinggo Regency Land Office and PPAT Josidara do not need to be withdrawn as the parties being sued, because these parties are only general officials whose task is to complete land administration as a result of the agreement made by the parties